1986
DOI: 10.1002/cne.902520209
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the cerebellum of normal‐reeler mutant mouse chimera

Abstract: The normal-reeler chimera mouse (+/+ in equilibrium with rl/rl) provides an experimental system in which an analysis of the migration of immature neurons in the cerebellum can be accomplished. In the present study, five chimera mice were produced from embryos of the wild-type control (C57Bl/6N) and the reeler mutant mouse (BALB/c) by the aggregation technique. The isozyme pattern of glucosephosphate isomerase (GPI) revealed that the brain tissue in the chimera contained both isozymes of the BALB/c (reeler) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…In most but not all of the folium of the cerebellar cortex, the alignment of Purkinje cells is disturbed by the lack of reelin protein that is secreted from granule cells (Miyata et al, 1997). The reeler mouse cerebellum is composed of mainly abnormal Purkinje cells, with nearly inverted or short bipolar dendrites in the central mass, where few neurite bundles are present (Rakic, 1975;Terashima et al, 1986), and small numbers of normal-like Purkinje cells distributed in peripheral quasinormal cerebellar cortex, where some parallel fibers are present (Sadler and Berry, 1989;Nagata and Terashima, 1994). Some of the Purkinje cells in the granular layer of the cortex, which appear to be similar to the cultured Purkinje cells shown in Figure 5I-K, extend long dendrites radially without branching up to the molecular layer, where it branches profusely (Rakic, 1975;Mariani et al, 1977).…”
Section: Disruption and Recovery Of Purkinje Cell Dendrite Orientatiomentioning
confidence: 98%
“…In most but not all of the folium of the cerebellar cortex, the alignment of Purkinje cells is disturbed by the lack of reelin protein that is secreted from granule cells (Miyata et al, 1997). The reeler mouse cerebellum is composed of mainly abnormal Purkinje cells, with nearly inverted or short bipolar dendrites in the central mass, where few neurite bundles are present (Rakic, 1975;Terashima et al, 1986), and small numbers of normal-like Purkinje cells distributed in peripheral quasinormal cerebellar cortex, where some parallel fibers are present (Sadler and Berry, 1989;Nagata and Terashima, 1994). Some of the Purkinje cells in the granular layer of the cortex, which appear to be similar to the cultured Purkinje cells shown in Figure 5I-K, extend long dendrites radially without branching up to the molecular layer, where it branches profusely (Rakic, 1975;Mariani et al, 1977).…”
Section: Disruption and Recovery Of Purkinje Cell Dendrite Orientatiomentioning
confidence: 98%
“…In one such case, an inside-outside gradient appears to be present, as the inner tiers contain neurons with a more elaborate maturational status than the outer tiers. Reeler-normal chimeras have also been produced and studied by Mikoshiba and collaborators (Mikoshiba et al 1985a,b;Terashima et al 1986). Unfortunately, the presence of Cajal-Retzius cells in the rudimentary MZ overlying this teratoma was not studied.…”
Section: The Action Of the Reeler Gene Is Intrinsic To The Neuroepithmentioning
confidence: 99%
“…1 A-C). Studies with normal-reeler chimeras have demonstrated that some of the Purkinje cells that are genetically reeler can be positioned normally, and conversely, Purkinje cells of normal origin are found ectopically (Mullen, 1978(Mullen, , 1984Terashima et al, 1986), suggesting that a cue(s) governing the normal alignment of Purkinje cells is extrinsic to Purkinje cells.…”
Section: Abstract: Cerebellum; Layer Formation; Cell Migration; Reelmentioning
confidence: 99%